Names and brief introductions of the standard-bearers of the Prophet’s (P.B.U.H) campaigns: غزوات نبوی ﷺ کے علمبرداروں کے اسماء و مختصر تعارف - Ibrahim , Shazia; Tareen, Dr. Pari Gul; Yaseen, Fozia (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This paper presents a concise overview of the flag bearers (Alambardar) in the battles (Ghazawat) of Prophet Muhammad (peace be upon him). The role of flag bearers was not merely symbolic but held immense strategic and motivational significance in Islamic warfare. This paper highlights the names and contributions of these distinguished companions who carried the banner of Islam in various battles, showcasing their bravery, loyalty, and unwavering faith. Among the prominent flag bearers were Hazrat Ali ibn Abi Talib, known for his unmatched valor; Hazrat Mus‘ab ibn Umair, who sacrificed his life while holding the flag at Uhud; Hazrat Zubair ibn al-Awwam, a courageous warrior of Islam; and Hazrat Sa‘d ibn Abi Waqqas, among others. Each of these companions played a crucial role in leading the Muslim forces, ensuring discipline, and boosting the morale of their fellow warriors. By examining their lives and contributions, this research aims to shed light on their pivotal roles in the early Islamic military campaigns and their lasting legacy in Islamic history.